2009
DOI: 10.1177/000348940911800206
|View full text |Cite
|
Sign up to set email alerts
|

Benign Paroxysmal Positional Vertigo: Concomitant Involvement of Different Semicircular Canals

Abstract: Multiple-canal BPPV was rare, and usually involved canals on the same side; simultaneous involvement of the posterior and lateral canals was much more common than involvement of the anterior and posterior canals or the anterior and lateral canals. Trauma increased the risk for multiple-canal BPPV, but not the risk for bilateral single-canal BPPV. Cupulolithiasis was not a factor in multiple-canal BPPV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
44
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 20 publications
10
44
0
2
Order By: Relevance
“…10 Tomaz et al reported 1.5 per cent multiple canal involvement and stated that trauma was the main risk factor. 11 In our series, multiple were diagnosed with pseudo-bilateral BPPV and they did not differ from patients with unilateral posterior canal BPPV in terms of clinical characteristics. However, trauma was a more common trigger than other known causes of BPPV.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…10 Tomaz et al reported 1.5 per cent multiple canal involvement and stated that trauma was the main risk factor. 11 In our series, multiple were diagnosed with pseudo-bilateral BPPV and they did not differ from patients with unilateral posterior canal BPPV in terms of clinical characteristics. However, trauma was a more common trigger than other known causes of BPPV.…”
Section: Discussionmentioning
confidence: 51%
“…12 Tomaz et al reported that more than 90 per cent of patients with multiple canal involvement had simultaneous involvement of the lateral and posterior canals on the same or on opposite sides, and all were canalolithiasis cases. 11 Lateral and posterior canal BPPV, either on the same or on the contralateral side, is the most common type of mixed canal BPPV. 13,14 We also observed the simultaneous occurrence of lateral and posterior canal BPPV.…”
Section: Discussionmentioning
confidence: 99%
“…An incidence of up to 10% of bilateral posterior canal BPPV among BPPV cases has been reported in several studies [2][3][4][5][6][7][8]. Thus if the Dix-Hallpike test should not be repeated with the opposite side when the test on initial side is positive, potential cases with bilateral posterior canal BPPV would not be diagnosed and treated appropriately.…”
mentioning
confidence: 99%
“…Multicanal BPPV may also simultaneously involve in the posterior and lateral canals, either on the same side or on 2 sides, with a reported incidence of up to 13% among BPPV cases [4][5][6][7][8]. Thus if the supine roll test to evaluate lateral canal BPPV should not be performed since the patient presents with a history corresponding BPPV and shows a positive DixHallpike test, potential cases with multicanal BPPV involving the posterior and lateral canals would not be diagnosed and treated appropriately.…”
mentioning
confidence: 99%
“…Despite the wealth of information about posttraumatic BPPV affecting the posterior and horizontal semicircular canals (16,17), the prevalence of AC and combined BPPV after head trauma often remains obscure. So far, there is only limited information indicating that head trauma is a risk factor for AC (10) and multiple-canal BPPV (18). In particular, posttraumatic combined AC/PC BPPV of the same labyrinth has rarely been described in the literature (19).…”
mentioning
confidence: 99%